Chinese Leadership - Wang, Barbara Xiaoyu (London Palgrave Macmillan, 2011)
With the accelerating integration of China into the global economy, there is a thirst to understand how Chinese managers like to lead and how Chinese employees like to be managed. There is no doubt that China can be a difficult and risky market for foreign businesses. The authors show managers how to succeed when doing business in China.
Includes index
Keywords: Leaderrship